Review of the 2019 resolutions of the Supreme Court Criminal Chamber concerning substantive criminal law (Ius Novum, 2021)
The article carries out an analysis of resolutions and rulings of the supreme Court Criminal Chamber passed as a result of appellate courts’ requests for fundamental interpretation of a statute within the scope of substantive criminal law. the analysis covers: the method of extraordinary mitigation of a penalty for felonies carrying cumulative deprivation of liberty and a fine (article 60 § 2 CC); a conditionally suspended cumulative penalty of deprivation of liberty and a penalty of limitation of liberty (article 87 § 1 CC), and admissibility of cumulating the penalty of deprivation of liberty and the penalty of limitation of liberty that substitutes for a conditionally suspended penalty of deprivation of liberty (article 75a § 1 CC); liability for an offence of failing to pay alimony (article 209 § 1 CC) connected with the modification of its statutory features laid down in act of 23 March 2017; the issue of parents’ liability for the offence of kidnapping or detaining a minor under the age of 15 or a physically or mentally disabled person against the will of a person granted the rights of their caretaker or guardian (article 211 CC).
Keywords: fine; cumulative penalty; penalty of limitation of liberty; penalty of deprivation of liberty; minors; extraordinary mitigation of a penalty; offence of failing to pay alimony; offence of kidnapping or detaining a minor under the age of 15